Incidental synchronous [99mTc] HYNIC-TOC avid lesion of the neck in a patient with metastatic melanoma: a metastatic lymph node or a carotid body tumor masquerading as a lymph node? - Vahid Roshanravan; Ehsan Soltani; Ehsan Hasanzadeh Hadad; Ramin Sadeghi; Azadeh Sahebkari; Mahdi Mottaghi; Atena Aghaee (Asia Oceania Journal of Nuclear Medicine and Biology, 2022)
A 53-years-old woman with a plantar malignant melanoma lesion was referred to our tertiary clinic for sentinel lymph node mapping. Lymphoscintigraphy with Tc-99m-Phytate detected ipsilateral inguinal and popliteal sentinel nodes. After total resection of nodes, the pathology report confirmed that all specimens were involved by the tumor. As part of an institutional study evaluating somatostatin receptor avidity of melanoma by Tc-99m-HYNIC-TOC scan, she also underwent a whole-body octreotide scan, which surprisingly showed intense tracer uptake in the right cervical region, confining in SPECT/CT images to a mass at the C2 spinal level, adjacent to the right carotid bifurcation. Neck surgery with gamma probe after injection of another dose of Tc-99m-HYNIC-TOC was performed successfully, and the pathology report was consistent with a carotid body tumor. To best our knowledge, our case is the first one in the literature, which reports an incidental paraganglioma with Tc99m-HYNIC-TOC scan which resected via radio-guided surgery, again with Tc99m-HYNIC-TOC tracer.